Induction of Cellular Genes Is Mediated by the Bel1 Transactivator in Foamy Virus-Infected Human Cells - Wagner, Andrea (American Society for Microbiology, 2000)
To gain insight into human foamy virus (HFV; also called spumaretrovirus)-induced alterations of cellular genes, the expression profiles of defined genes in HFV-infected primary human cells were analyzed by cDNA array assays. Several distinct cellular genes activated by HFV infection were identified; the identities of the cellular genes were confirmed by RNA blot analyses. Compared with mock-infected controls, the concentrations of cellular Kip2, Egr-1, COUP-TF1, insulin-like growth factor II (IGF-II), and EphB3 mRNAs were significantly increased in HFV-infected cells and showed a gene-specific and time-dependent induction. Immunoblot analyses with antibodies against some of the cellular gene products revealed increased levels of the corresponding proteins. To investigate mechanisms of HFV-induced alterations in cellular gene expression, the capacity of known HFV genes to increase expression of defined cellular genes was analyzed by transient expression experiments. Plasmids that encode the HFV Bel1 transcriptional transactivator were necessary and sufficient to strongly increase expression of p57Kip2, IGF-II, and EphB3 genes in 293T cells. Potential mechanisms and consequences of activation of cellular genes during HFV infection and Bel1 transactivation of the Kip2 gene are discussed.